Cannabis and cognitive functioning - Solowij, Nadia (Cambridge University Press, 1998)
Cannabis is the most widely used illicit substance in the world, but the question of whether its long term use can result in lasting and irreparable cognitive impairment remains controversial. This timely and well-argued volume provides an extensive and comprehensive critical review of the literature relevant to cannabis and cognitive functioning, examining the evidence in the light of important recent findings in the pharmacology and neuropsychology of cannabis. Original studies conducted by the author are presented, utilizing one of the most modern and sensitive techniques available to assess cognitive functioning--the use of event-related potentials or ERPs. The author\'s conclusion, that long term cannabis use may produce irreversible impairment in memory, attention and the organization and integration of complex functions, will be of compelling interest to a wide range of clinicians, researchers and policy makers.
International research monographs in the addictions
Keywords: Evoked Potentials; Cognition Disorders; psychologie, klinická psychologie; psychiatrie; Cannabis; kognitivní poruchy; evokované potenciály